Teen Suicide Prevention - Ravinder K Gupta; Vivek Pandita; Urvi Gupta (Dr. Annil Mahajan, 2024)
Suicide is "any self-destructive behaviour that has an intent to seriously damage oneself or cause death". It is the second leading cause of death among adolescents. India reported the highest suicide rate in 2021 with 12 suicides for every 100,000 population. Furthermore, this trend, according to Indian National Crime Records Bureau (NCRB) has risen at the rate of 6.2% compared to the year 2020. The interaction between multiple factors like biological, psychological, socio cultural, and family-like factors can cause contribute to suicide in teens. The increase in suicide rates among females could be attributed to gender specific stressors, violence, and discrimination. The rise in male suicide rates could be attributed to financial strain, academic pressure, and substance abuse.